Migration, mediums and magic : a spirit-medium temple’s encounter and negotiation with Buddhism in post-independence Singapore - Soh, Esmond Chuah Meng (Nanyang Technological University, 2019)
This thesis is a microhistorical study of how the strategies and belief systems of a spirit-medium temple were transformed as its leadership positioned the organisation within a changing Chinese religious landscape. Notably, this syncretic temple existed in contrast to the Reformist Buddhist movement, which became established in post-independence Singapore. I defend two inter-related arguments in this thesis. Firstly, this temple endeavoured to identify itself as a unique Buddhist spirit-medium temple, where Buddhism became absorbed into the temple’s all-encompassing syncretism. Secondly, this temple rejected assimilating into Reformist Buddhism despite the latter’s growing prominence. When differences appeared too protuberant, the temple expanded into Malaya to develop spirit-mediumship away from the constraints of Reformist Buddhism in Singapore. Through charting this temple’s history, this study explores the history of Chinese religion within Singapore and the broader Chinese diaspora since the early twentieth century. In doing so, this thesis reveals the limitations of interpreting syncretic religion solely from the perspective of organised religious categories. Furthermore, this microhistory demonstrates how Chinese syncretic religious institutions have challenged the hegemony of homogenising religious movements by negotiating independent identities for themselves. I conclude by suggesting how this study can provide a means of understanding similar syncretic religious organisations.